Stunned myocardium - Ristić Anđelka; Damjanović Milorad; Baškot Branislav; Matunović Radomir (Vojnosanitetski Pregled, 2005)
Background. Stunned myocardium is a state of delayed recovery of regional contractility after a transient period of ischemia followed by reperfusion. Case report. A 67-year-old patient was admitted to our hospital with acute anterior myocardial infarction, and treated using percutaneous transluminal coronary angioplasty (PTCA) within acute disease stage. Reversible myocardial dysfunction persisted after ischemia following the return of normal perfusion. Abnormal resting wall motion with augmentation of contractility at low and high doses of dobutamine characterizes the stunned myocardium and reflects the normal blood flow reserve, characteristic for these postischemic, reperfused segments. SPECT (Single Photon Emission Computerized Tomography) with Tc 99 and dipyradamole showed normalization of perfusion defects in the apical region. Theree months after the infarction and PTCA, contractility was almost completely recovered. Conclusion. Stunned myocardium recovery lasted from few weeks to few months. Control ultrasonography as well as SPECT showed normalization of systolic function of the left ventricle in the viable segments registered at previous examinations.